2007
DOI: 10.2320/matertrans.48.10
|View full text |Cite
|
Sign up to set email alerts
|

Structural Changes of Precipitates in an Mg-5 at%Gd Alloy Studied by Transmission Electron Microscopy

Abstract: Structural changes of precipitates in an Mg-5 at%Gd (Mg 95 Gd 5 ) alloy by aging at 200 C and 250 C have been studied by ordinary highresolution transmission electron microscopy (HRTEM) and high-angle annular detector dark-field scanning transmission electron microscopy (HAADF-STEM). In the early stage of precipitation by aging at 200 C up to 5 h, a short-range ordered structure exists in Gd-enriched regions with an about 2 nm size, and nuclei of an Mg 7 Gd structure ( 0 phase) occur in the short-range ordered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
61
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(74 citation statements)
references
References 13 publications
10
61
0
3
Order By: Relevance
“…1,2) Recently, structural changes of precipitates have been studied for an aged Mg-5 at% Gd alloy in detail by the combination of HRTEM and HAADF-STEM. 3,4) A short-range ordered structure at the early stage of aging and a new crystal structure of Mg 7 Gd for 0 precipitates at peak aging have been proposed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2) Recently, structural changes of precipitates have been studied for an aged Mg-5 at% Gd alloy in detail by the combination of HRTEM and HAADF-STEM. 3,4) A short-range ordered structure at the early stage of aging and a new crystal structure of Mg 7 Gd for 0 precipitates at peak aging have been proposed.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, HAADF-STEM has been shown to be a powerful tool for the investigation of fine phases precipitated coherently to the matrix and for direct observations of heavy atoms segregated from solid solutions. 3,4,12,13) …”
Section: Introductionmentioning
confidence: 99%
“…Recently, Nishijima et.al. detailed examinations on the precipitation behaviours of Mg-Gd and Mg-Y alloy by high angle annular dark field-scanning transmission electron microscopy (HAADF-STEM) technique [3,4]. They concluded that the arraignment of bright dots indicates the short range ordered state and the β' phase nuclide in the short range ordered structure.…”
Section: Introductionmentioning
confidence: 99%
“…1,2) According to the literature, 38) the following precipitation sequences have been reported in MgRE systems: The precipitation sequence in MgRE alloys has been also investigated by high resolution transmission electron microscopy (HRTEM) and high angle annular dark field scanning transmission electron microscopy (HAADF-STEM) in detail. 7,8,1116) Among these work, very few are focused on the MgGdY system and the early path of precipitation still remains unclear. In comparison to the binary MgGd alloys, MgGdY (GY series), developed for practical Mg alloys by Kamado et al 9,10) to reduce the density, exhibit an increased creep resistance up to 523573 K. In this work, the early stages of aging in MgGdY alloy have been observed by HAADF-STEM in order to elucidate the mechanisms involved during the early stages decomposition of the supersaturated solid solution, and the comparison between HRTEM and HAADF-STEM images obviously shows the possibility of HAADF-STEM to clarify the precipitation sequence.…”
Section: Introductionmentioning
confidence: 99%